Design and Simulation Analysis of Variable Speed Surface of Cage-free Bearing - ZHAO Yan-ling; ZHANG Xiao-nan; QIN Sheng (Journal of Harbin University of Science and Technology)
During the operation of cage-free bearing, the contact collision between the adjacent rollers may reduce the bearing life. Therefore, this paper propose the design of variable speed surface in outer ring raceway so that rollers can decelerate and accelerate regularly, and then rollers can be dispersed automatically. This paper specifically analyzes the time-varying displacement law of rolling body under radial load and the force between each bearing component. Based on Hertz theory, the equation of contact force between the roller and variable speed surface is established, and the variation of contact force during the rolling motion is revealed to determine the circumferential span angle of variable speed surface, which can be used to design the structural parameters of variable speed surface. Based on simulated analysis of the improved cage-free bearing geometry parameters, this work verifies the correctness of structural parameters design of variable speed surface by analyzing and comparing the changing curves that the dispersion spacing of any three groups adjacent roller and acceleration of any roller. The research results of this paper have certain guiding significance for the design of cage-free bearing.